2018
DOI: 10.17221/86/2017-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of environmentally safe food additives and food supplements in an in vitro growth inhibition of significant Fusarium, Aspergillus and Penicillium species

Abstract: Akköprü A., Özaktan H. (2018): Identification of rhizobacteria that increase yield and plant tolerance to angular leaf spot disease in cucumber. Plant Protect. Sci., 54: 67-73.The biological control of angular leaf spot disease (ALS) of cucumbers (Cucumis sativus), caused by pseudomonas syringae pv. lachrymans (psl), using promising rhizobacteria (RB) and to compare RB efficacy to that of acibenzolar-S-methyl (ASM) was investigated. Effects of ASM and RB isolate pseudomonas putida AA11/1 that was isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Some studies mention the more likely indirect secondary effect of chitosan applied to plants, such as the increased resistance of plants thanks to the elicitation of defensive mechanisms in the tissue, together with the mechanical barrier of the polymer chitosan layer [25,26]. However, our abovementioned previous study also confirmed the significant direct in vitro antifungal effect of chitosan [5], which was also experimentally confirmed in the case of P. infestans in this study. The efficacy of chitosan is most probably caused by many mechanisms, such as the electrostatic interaction of positively charged molecules of chitosan with cellular membranes.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Some studies mention the more likely indirect secondary effect of chitosan applied to plants, such as the increased resistance of plants thanks to the elicitation of defensive mechanisms in the tissue, together with the mechanical barrier of the polymer chitosan layer [25,26]. However, our abovementioned previous study also confirmed the significant direct in vitro antifungal effect of chitosan [5], which was also experimentally confirmed in the case of P. infestans in this study. The efficacy of chitosan is most probably caused by many mechanisms, such as the electrostatic interaction of positively charged molecules of chitosan with cellular membranes.…”
Section: Discussionsupporting
confidence: 86%
“…The great antifungal potential of chitosan hydrochloride has already been described in our previous studies [5]. In the specified case, excellent inhibitory values were achieved on model filamentous fungi from the pathogenic and toxicogenic groups Aspergillus, Fusarium, and Penicillium [5]. However, we did not expect such excellent results, particularly against the evolutionarily and biologically different pathogen P. infestans (Oomycetes) [21], mainly due to the complicated biology of this pathogen as well as the very different infectious stages in the process of pathogenesis itself [22].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations